2021
DOI: 10.1086/714506
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Toxicity of Plastic Leachates as a Function of Weathering and Polymer Type: A Screening Study with the Copepod Nitocra spinipes

Abstract: The production and use of plastic over many decades has resulted in its accumulation in the world's oceans. Plastic debris poses a range of potential risks to the marine environment and its biota. Especially, the potential hazards of small plastic debris and chemicals associated with plastic have not been extensively studied. When buoyant plastic is exposed to ultraviolet radiation, it will slowly degrade and leach chemicals into surrounding waters. These leachates can include additives, sorbed organic polluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
(63 reference statements)
3
18
0
Order By: Relevance
“…Although data are scarce and our knowledge is based exclusively on pure polymers, the impacts of photochemical weathering appear to be mixed. A couple of studies reported that exposure of plastic to sunlight increased toxicity, 68,69 one reported no major impact, 70 and another reported decreased toxicity. 71 Our collective findings indicate that a comprehensive and accurate understanding of the fate and impacts of marine plastic pollutiona critical step toward establishing evidence-based policies and developing next-generation materialsrequires the research community to embrace the diverse formulations and sunlight-driven transformations of plastics in the environment.…”
Section: Characterization Of Plastic Opticalmentioning
confidence: 99%
“…Although data are scarce and our knowledge is based exclusively on pure polymers, the impacts of photochemical weathering appear to be mixed. A couple of studies reported that exposure of plastic to sunlight increased toxicity, 68,69 one reported no major impact, 70 and another reported decreased toxicity. 71 Our collective findings indicate that a comprehensive and accurate understanding of the fate and impacts of marine plastic pollutiona critical step toward establishing evidence-based policies and developing next-generation materialsrequires the research community to embrace the diverse formulations and sunlight-driven transformations of plastics in the environment.…”
Section: Characterization Of Plastic Opticalmentioning
confidence: 99%
“…Moreover, decreased swimming activities were observed in the positive control with NaCl, whereas the chemicals leaching from the tested microplastics (SB foil and LDPE-R) did not result in adverse effects. In general, the exposure of the shrimps to the leachates from (un)weathered LDPE-R and SB microplastics resulted in varied swimming activities, which is in accordance with the results by Qiu et al (2022) but in contrast to what has been reported by Gewert et al (2021). Finally, performed a metaanalysis on locomotor behaviors for aquatic organisms that were exposed to plastic particles and their chemicals.…”
Section: Uv-induced Changes Of the Leachate Toxicitysupporting
confidence: 86%
“…8,10 This leaching into the environment is concerning as many functional organic plastic additives have been associated with health effects such as different cancers, endocrine disruption, adverse effects to reproduction and development, as well as general toxicity in a variety of organisms. 1,2,12,13 Given their potential toxicity and detection in the environment, some plastic additives have been identied as potential contaminants of concern or even as persistent organic pollutants (POPs). 13 Nevertheless, many hazardous plastic additives are not restricted.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 This leaching into the environment is concerning as many functional organic plastic additives have been associated with health effects such as different cancers, endocrine disruption, adverse effects to reproduction and development, as well as general toxicity in a variety of organisms. 1,2,12,13…”
Section: Introductionmentioning
confidence: 99%